2010
DOI: 10.1016/j.ygcen.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed production of methyl farnesoid hormones yields developmental defects and lethality in Drosophila larvae

Abstract: A long-unresolved question in the developmental biology of Drosophila melanogaster has been whether methyl farnesoid hormones secreted by the ring gland are necessary for larval maturation and metamorphosis. In the present study, we have used RNAi techniques to inhibit 3-Hydroxy-3-Methylglutaryl CoA Reductase (HMGCR) expression selectively in the corpora allatal cells that produce the circulating farnesoid hormones. The developing larvae manifest a number of developmental, metabolic and morphogenetic derangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Methyl farnesoate (MF), an unepoxidated sesquiterpenoid related to insect juvenile hormone (JH), accumulates in Drosophila (Jones et al, 2013), has been reported to bind to USP with nanomolar affinity (Jones et al, 2006), and RNAi-mediated suppression of farnesoid production in Drosophila induces larval lethality and defects in molting (Jones et al, 2010). MF is widely distributed in crustaceans, and implicated in a variety of endocrine signaling functions during embryonic and larval development, growth, sex determination and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl farnesoate (MF), an unepoxidated sesquiterpenoid related to insect juvenile hormone (JH), accumulates in Drosophila (Jones et al, 2013), has been reported to bind to USP with nanomolar affinity (Jones et al, 2006), and RNAi-mediated suppression of farnesoid production in Drosophila induces larval lethality and defects in molting (Jones et al, 2010). MF is widely distributed in crustaceans, and implicated in a variety of endocrine signaling functions during embryonic and larval development, growth, sex determination and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl farnesoate is found in larvae, but is 100 times less active than JH III in preventing metamorphosis when applied at the time of pupariation [32]. When synthesis of methyl farnesoate and thus of all JHs is prevented in Drosophila by expression of HMGCoA reductase RNAi, most larvae die during the molt to the 3rd larval stage [30]. When these larvae were fed farnesol, they could ecdyse to the 3rd instar and at higher concentrations of farnesol could pupariate, but neither methyl farnesoate nor JH III alone had this effect [30,32].…”
Section: Jh Receptormentioning
confidence: 99%
“…When synthesis of methyl farnesoate and thus of all JHs is prevented in Drosophila by expression of HMGCoA reductase RNAi, most larvae die during the molt to the 3rd larval stage [30]. When these larvae were fed farnesol, they could ecdyse to the 3rd instar and at higher concentrations of farnesol could pupariate, but neither methyl farnesoate nor JH III alone had this effect [30,32]. Importantly, USP null mutants die during the molt to the 2nd instar as pharate 2nd instar larvae showing double mouthhooks and spiracles [57].…”
Section: Jh Receptormentioning
confidence: 99%
“…The CAX larvae undergo the expected two larval molts, but because we sometimes see remains of degenerating CA cells at the start of the last larval stage, we cannot conclude anything about the requirements of JH for these larval molts. Recently, Jones et al, using 3-hydroxy-3-methylglutaryl CoA reductase (HMGCR) RNAi to depress the level of JH and its farnesoid precursors in early larvae, showed that the larvae mainly die during the molt to the third instar (Jones et al, 2010), indicating that JH may be required for that molt. The destruction of the CA by the third instar allowed us to examine the role of JH during the last instar and early metamorphosis.…”
Section: Research Articlementioning
confidence: 99%